Using a shared research practices paradigm with adult choral singers for the teaching and learning of musical literacy skills - Hiney, Aoife (2022)
This paper discusses the development of music lessons for adults in a non-professional choir. Based on the Kodály Concept, the lessons took place from April 2019 until March 2020. The singers and conductor engaged in shared research practices, tracking teaching and learning experiences through journaling and sharing our writings. Through this sharing, we have discussed the activities that are most enjoyable, difficulties we have encountered, and how we might overcome these difficulties. The data has important implications for my own practice as a music teacher and conductor, in addition to resonating with topics such as critical geragogy and life-long learning in non-academic contexts. Furthermore, shared research practices give adult learners an opportunity to actively engage in teaching and learning processes, with implications for future projects that include adult music education in non-academic contexts.